2021
DOI: 10.1177/17479541211030076
|View full text |Cite
|
Sign up to set email alerts
|

How football team composition constrains emergent individual and collective tactical behaviours: Effects of player roles in creating different landscapes for shared affordances in small-sided and conditioned games

Abstract: The aim of the present study was to examine how team composition of players with different roles constrains individual and collective tactical behaviours, and ball possession effectiveness, during competitive 3 vs 3 small-sided and conditioned games (SSCGs) in youth soccer players. Fifteen male players (under 15 yrs, mean age 13.2 ± 1.03 years, mean years of practice: 4.2 ± 1.10 years) from the same club participated in this study. For analysis purposes, on advice from the coaching staff, participants were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Moreover, the results can be discussed from an ecological dynamics perspective. Previous studies revealed that a players’ main playing position (e.g., defender, midfielder, or forward) has a significant influence on the technical-tactical elements in soccer ( Laakso et al, 2019 , 2021 ). Therefore, from an ecological dynamics perspective, when considering the results, it must be taken into account that the main player position has an influence on the perception-action systems of soccer players ( Araújo et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the results can be discussed from an ecological dynamics perspective. Previous studies revealed that a players’ main playing position (e.g., defender, midfielder, or forward) has a significant influence on the technical-tactical elements in soccer ( Laakso et al, 2019 , 2021 ). Therefore, from an ecological dynamics perspective, when considering the results, it must be taken into account that the main player position has an influence on the perception-action systems of soccer players ( Araújo et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…To be more precise, the players in this sample are regulars at different main positional roles and, therefore, cannot be assigned to a single specific main playing position. From an ecological dynamics perspective, it would be profitable to test the findings of Laakso et al (2019 , 2021) using such special player samples. The results from such studies might indicate in what way these theories also apply to this particular type of player.…”
Section: Discussionmentioning
confidence: 99%
“…Although we demonstrate that self-organisation of the cones by children increased the number of touches accrued in conditions of greater proximity, we did not examine whether this process might influence game performance. There is evidence, from a study of 15 male youth players, that team composition (e.g., fielding midfielders versus attackers) in small-sided games can influence the players’ capability of action that emerges during performance [ 36 ]. Whether self-organisation of practice in the way we operationalised in the present study translates into game performance is a natural progression from the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that longer possessions led to a higher number of passes, touches per possession, shots, dribbles and final third entries [ 8 ]. When we consider the midfielders playing role, this playing position is characterized by players that can control the game pace and responsible for progressing with the ball to further zones in the pitch throw travelling with, performing penetrative passes or receiving the ball between defensive spaces [ 18 , 20 , 28 ]. Therefore, it is not surprising that the variables that discriminated the longer from shorter sequence were mainly related to passing actions (i.e., successful passes, lateral, backward, and rupture passes) and the number of touches per possession.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous considerations, this study adopted a team configuration design that only accounted for the players’ playing position (e.g., grouping fullbacks with central defenders). The conditions were tested during a Gk+3vs3+Gk SSG performed in a 30x25m pitch [ 27 , 28 ] and based on a 5-min duration each bout interspersed with a 10-min passive rest in between [ 28 , 29 ]. A regulation ball size was used in all situations, and the SSG included two regular size goals (2.44 m x 7.32 m).…”
Section: Methodsmentioning
confidence: 99%